THE IMPACT OF ADIPOKINES IN THE ONSET OF ATRIAL FIBRILLATION. (April 2021) - Papadopoulos, Dimitrios; Sanidas, Elias; Velliou, Maria; Tsakalis, Konstantinos; Zerva, Kanella; Kyrana, Panagiota; Iliopoulos, Dimitrios; Mantzourani, Marina; Toutouzas, Konstantinos; Barbetseas, John
Abstract : Objective: Several adipose tissue bioactive factors (adipokines) have been linked to cardiovascular (CV) diseases. Apelin and omentin-1 have cardioprotective effects whereas visfatin and chemerin have negative effects on CV function. The aim of this study was to calculate apelin, omentin-1, visfatin and chemerin plasma levels in patients with a first episode of atrial fibrillation (AF) investigating any potential association of these factors with the presence of the arrhythmia. Figure. No caption available. Design and method: Overall, 60 patients without a previous history of AF were studied. Of them, 30 had a first documented episode of AF on ECG or 24-hour Holter monitoring during the last month and 30 did not. Apelin, omentin-1, visfatin and chemerin plasma levels were measured by the Elisa method. Results: Compared to non-AF patients, visfatin and chemerin levels were higher in patients with a first episode of AF while apelin and omentin-1 levels were lower. However, statistically significant differences were observed only for apelin and visfatin. No statistically significant differences in demographic characteristics and CV risk factors were noted between the two groups (Table). Conclusions: Visfatin as a non-cardioprotective adipokine was increased in patients having AF for the first time while apelin as a cardioprotective adipokine was decreased indicating a potential correlation of these hormones with the presence of the arrhythmia.